Dairy farmers' risk attitudes and their perceptions towards environmental risks in Northwest Turkey - Özsayın, Damla (Emirates Journal of Food and Agriculture, 2023)
This study aims to determine the factors that affect dairy farmers' risk attitudes and their perceptions towards environmental risks in Northwest Turkey. By the proportional sampling method, data were collected from 381 dairy farmers. The survey was performed from September 2020 to June 2021. The study data were evaluated by descriptive statistics, risk matrix method, equally likely certainty equivalent method and probit model. In this study, severe storm, excessive rainfall/flood, livestock diseases, high temperature and drought was posed an important risk for dairy farmers. The majority of them showed risk aversion behaviour. Age, education level, household size, dairy farming experience, the number of dairy cattle, the land ownership status, livestock insurance and access of agricultural credits had a significant effect on risk perceptions and attitudes of dairy farmers. As a result, these findings are expected to ensure contribution to rural development, province and region economy, insurance institutions, agricultural policy makers, and further emphasizing the importance of environmental risks in dairy farming activity